PELAKSANAAN PELATIHAN TES CALON PEGAWAI NEGERI SIPIL (CPNS) DENGAN SISTEM COMPUTER ASSISTED TEST (CAT) PADA LEMBAGA KURUS PELATIHAN (LKP) CORIEN CENTER - Ejra Oktutula; Agus Zainal Ramat; Sofino Sofino (Jurnal Pendidikan Sepanjang Hayat, 2019)
The purpose of this study was to determine how the implementation of CPNS test on Corien Center LKP in Bengkulu City with research problems which included persriapan, trained preparation’s, how the trainer demonstrated the material and the traine’s efforts so that participants could practice the material in conducting test training CPNS system (CAT) Computer Assisted Test on LKP Corien Center used research with a case study method, data collection was carried out through interviews, observation and documentation. To test the data validation the researcher used triangulation techniques. The informants in this study were four people. Based on the results of the discussion, it can be concluded that : the trainer must prepare in the implementation of the training, namely modules (whiteboard markers and erasers), in the implementation of CPNS system test training (CAT) Computer Assisted Test on the Corien Center LKP the training participants must prepare, namely learning equipment in the form (pens, nptebooks) and bring the modules peovided by the institution, in the implementation of the training the tainers demonstrate the training  material that is mastering the training material and preparing the necessary media so that the deliverwd material can be distributed to trainees, then in the implementation of an effort training carried out by the trainer so that the training participants could (CAT) Computer Assisted Test on the Corien Center LKP that is by using a method and strategy that is suitable whit teaching and learning activities. Keywords : CPNS CAT Test Training LKP Corien Center